Electrophotographic apparatus, process cartridge, and image forming method

JP7636960B2Active Publication Date: 2025-02-27CANON KK
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
JP2021082779
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-14
Publication Date
2025-02-27
Estimated Expiration
2041-05-14

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、使用開始初期に高温高湿環境下で低印字率の画像形成が連続した場合においても、クリーニングの安定性を向上させることができる電子写真装置を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636960000028
    Figure 0007636960000028
  • Figure 0007636960000029
    Figure 0007636960000029
  • Figure 0007636960000030
    Figure 0007636960000030
Patent Text Reader

Abstract

To provide an electro-photographic device which can improve the stability of cleaning when image formation with a low printing rate continues under a high temperature-high humidity environment at an early stage of the use start.SOLUTION: An electro-photographic device comprises: an electro-photographic photoreceptor; charging means; image exposure means; development means which has toner; transfer means; and cleaning means. The surface of the electro-photographic photoreceptor is formed of hydrogenated amorphous silicon carbide or hydrogenated amorphous carbon. Toner has toner particles. The toner particles contain a specific resin A. The resin A is the crystalline resin. The content ratio of a unit indicated by the following formula (1) in the resin A is between 30 mass% and 100 mass% with respect to the total mass of the resin A.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrophotographic apparatus, a process cartridge, and an image forming method, and more particularly to an electrophotographic apparatus, a process cartridge, and an image forming method using an electrophotographic photosensitive member whose surface is formed of hydrogenated amorphous silicon carbide or hydrogenated amorphous carbon. [Background technology]

[0002] Electrophotographic image forming methods (hereinafter also simply referred to as "image forming methods") and electrophotographic devices using the same are widely and commonly used as copying machines, facsimile machines, and printers. In such electrophotographic devices, the surface of an electrophotographic photoreceptor provided with a photoconductive layer is uniformly charged, and exposed to a laser or LED according to image information to form an electrostatic latent image on the surface of the electrophotographic photoreceptor. Then, toner is attached to the formed electrostatic latent image to form a toner image on the surface of the electrophotographic photoreceptor, which is then transferred to a transfer material such as paper to form an image.

[0003] As an electrophotographic photoreceptor that can be suitably used in such electrophotographic devices, an amorphous silicon electrophotographic photoreceptor that uses hydrogenated amorphous silicon in the photoconductive layer is known. Note that hydrogenated amorphous silicon is also abbreviated as "a-Si:H," electrophotographic photoreceptor as "photoreceptor," and amorphous silicon electrophotographic photoreceptor as "a-Si photoreceptor."

[0004] The Vickers hardness of the a-Si photoconductor is 1000kgf / mm 2 It is extremely hard and has excellent durability, heat resistance, and environmental stability, and is therefore preferably used in high-speed machines that require high reliability.

[0005] On the other hand, since a-Si photoconductors hardly wear out, their surface has high friction resistance, which can cause the cleaning blade to break and lead to image defects. To solve this problem, a technique for roughening the surface of the a-Si photoconductor is known (Patent Document 1). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 6619433 Summary of the Invention [Problem to be solved by the invention]

[0007] As a result of extensive research, the present inventors have found that the toner and its external additives act as lubricants in the nip portion of the cleaning blade, and play a role in stabilizing the frictional resistance of the blade. However, since almost no lubricant such as toner or its external additives is present in the nip portion of the blade in the early stage of use, there is room for improvement in the stability of cleaning in the early stage of use.

[0008] If some kind of lubricant is applied to the surface of a new blade in advance, cleaning may be stable for a while in the beginning. However, in a configuration that does not have a means for actively supplying lubricant, the lubricant that has been applied in advance is gradually lost with use. For this reason, cleaning may become unstable until toner and its external additives are sufficiently supplied as lubricant to the nip part. In particular, in a configuration in which the surface of an inorganic material such as an a-Si photoconductor is scraped with a rubber blade, it was found that when the lubricant runs out, the friction force in the scrape is very high and cleaning tends to become unstable. As a result, when images with low printing ratios are continuously formed in a high-temperature, high-humidity environment in the early stages of use, there is still room for further improvement in terms of cleaning stability. [Means for solving the problem]

[0009] An electrophotographic apparatus according to one aspect of the present invention for solving the above-mentioned problems includes an electrophotographic photosensitive member, charging means for charging the surface of the electrophotographic photosensitive member, image exposure means for irradiating the charged surface of the electrophotographic photosensitive member with image exposure light to form an electrostatic latent image on the surface of the electrophotographic photosensitive member, developing means having a toner and developing the electrostatic latent image with the toner to form a toner image on the surface of the electrophotographic photosensitive member, transfer means for transferring the toner image from the surface of the electrophotographic photosensitive member to a transfer material in a transfer step, and a cleaning means for removing residual toner remaining on the surface of the electrophotographic photosensitive member after the transfer step. The electrophotographic device has a cleaning means and a fixing means for fixing the toner image to the transfer material, the surface of the electrophotographic photoreceptor is formed of hydrogenated amorphous silicon carbide or hydrogenated amorphous carbon, the toner has toner particles, the toner particles contain a resin A having a unit represented by the following formula (1), the resin A is a crystalline resin, and the content ratio of the unit represented by the following formula (1) in the resin A is 30 mass % or more and 100 mass % or less with respect to the total mass of the resin A. [ka] (In formula (1), R 11 represents a hydrogen atom or a methyl group, and R 12 represents an alkyl group having 18 to 36 carbon atoms.

[0010] Further, a process cartridge according to another embodiment of the present invention is a process cartridge which integrally supports an electrophotographic photosensitive member, a developing means which has a toner and develops an electrostatic latent image on the surface of the electrophotographic photosensitive member with the toner to form a toner image on the surface of the electrophotographic photosensitive member, and a cleaning means which removes residual toner remaining on the surface of the electrophotographic photosensitive member after a transfer step, and is detachable from a main body of an electrophotographic apparatus, characterized in that the surface of the electrophotographic photosensitive member is formed of hydrogenated amorphous silicon carbide or hydrogenated amorphous carbon, the toner has toner particles, the toner particles contain resin A having a unit represented by the above formula (1), the resin A is a crystalline resin, and the content ratio of the unit represented by the above formula (1) in resin A is 30% by mass or more and 100% by mass or less with respect to the total mass of resin A.

[0011] Furthermore, an image forming method according to yet another embodiment of the present invention is an image forming method comprising: a charging step of charging the surface of an electrophotographic photoreceptor; an image exposure step of irradiating the charged surface of the electrophotographic photoreceptor with image exposure light to form an electrostatic latent image on the surface of the electrophotographic photoreceptor; a developing step of developing the electrostatic latent image with toner to form a toner image on the surface of the electrophotographic photoreceptor; a transfer step of transferring the toner image from the surface of the electrophotographic photoreceptor to a transfer material; and a cleaning step of removing residual toner remaining on the surface of the electrophotographic photoreceptor after the transfer step, wherein the surface of the electrophotographic photoreceptor is formed of hydrogenated amorphous silicon carbide or hydrogenated amorphous carbon, the toner has toner particles, the toner particles contain resin A having a unit represented by the above formula (1), the resin A is a crystalline resin, and the content ratio of the unit represented by the above formula (1) in resin A is 30 mass % or more and 100 mass % or less with respect to the total mass of resin A. Hereinafter, hydrogenated amorphous silicon carbide will be abbreviated as "a-SiC:H" and hydrogenated amorphous carbide will be abbreviated as "aC:H." Effect of the Invention

[0012] According to the present invention, it is possible to provide an electrophotographic apparatus capable of improving the stability of cleaning even when images are continuously formed at a low printing ratio in a high-temperature and high-humidity environment in the early stages of use. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic diagram for explaining an image forming method by an electrophotographic apparatus using an a-Si photosensitive member. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a layer structure of an a-Si photoconductor. [Diagram 3] FIG. 1 is a schematic diagram showing an example of a deposition apparatus for an electrophotographic photosensitive member by an RF plasma CVD method using a high-frequency power source, which can be used for producing an a-Si photosensitive member. [Figure 4] FIG. 1 is a schematic diagram illustrating an example of an electrophotographic apparatus having a process cartridge equipped with an electrophotographic photosensitive member. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The electrophotographic apparatus according to the present invention includes an electrophotographic photoreceptor, a charging unit, an image exposure unit, a developing unit, a transfer unit, a cleaning unit, and a fixing unit. In the electrophotographic apparatus according to the present invention, the charging unit charges the surface of the electrophotographic photoreceptor. The image exposure unit irradiates the charged surface of the electrophotographic photoreceptor with image exposure light to form an electrostatic latent image on the surface of the electrophotographic photoreceptor. The developing unit has a toner and develops the electrostatic latent image with the toner to form a toner image on the surface of the electrophotographic photoreceptor. The transfer unit transfers the toner image from the surface of the electrophotographic photoreceptor to a transfer material in a transfer step. The cleaning unit removes residual toner remaining on the surface of the electrophotographic photoreceptor after the transfer step. The fixing unit fixes the toner image to the transfer material. The surface of the electrophotographic photoreceptor is formed of hydrogenated amorphous silicon carbide or hydrogenated amorphous carbon. The toner has toner particles, and the toner particles contain a resin A having a unit represented by the following formula (1), the resin A being a crystalline resin, and the content ratio of the unit represented by the following formula (1) in the resin A is 30 mass % or more and 100 mass % or less with respect to the total mass of the resin A. [ka] (In formula (1), R 11 represents a hydrogen atom or a methyl group, and R 12 represents an alkyl group having 18 to 36 carbon atoms.

[0015] Further, an image forming method according to the present invention is a method using the electrophotographic apparatus according to the present invention described above, and includes a charging step of charging the surface of an electrophotographic photosensitive member, an image exposure step of irradiating the charged surface of the electrophotographic photosensitive member with image exposure light to form an electrostatic latent image on the surface of the electrophotographic photosensitive member, a developing step of developing the electrostatic latent image with toner to form a toner image on the surface of the electrophotographic photosensitive member, a transfer step of transferring the toner image from the surface of the electrophotographic photosensitive member to a transfer material, and a cleaning step of removing residual toner remaining on the surface of the electrophotographic photosensitive member after the transfer step.

[0016] The present inventors consider the mechanism by which the electrophotographic apparatus according to the present invention solves the problems to be as follows. As mentioned above, when the blade is first used, there is almost no lubricant such as toner or its external additives in the nip of the blade. If some kind of lubricant is applied to the surface of a new blade in advance, cleaning may be stable for a while in the early stages. However, in a configuration that does not have a means for actively supplying lubricant, the initial lubricant is gradually lost with use. For this reason, cleaning may become unstable until toner and its external additives are sufficiently supplied as lubricant to the nip portion. In particular, in a configuration in which the surface of an inorganic material such as an a-Si photoconductor is scraped with a rubber blade, it was found that when the lubricant runs out, the frictional force during scraping is very high and cleaning tends to become unstable.

[0017] For this reason, if image formation with an extremely low printing rate continues immediately after the start of use, toner, external additives, etc. are hardly supplied to the nip part of the blade, and the lubricant in the nip part continues for a long period of time. Furthermore, if the usage environment is a high temperature and high humidity environment, the friction force tends to be high due to the influence of moisture adsorbed on the surface, which makes cleaning even more unstable. If cleaning becomes unstable, the frictional force between the cleaning blade and the electrophotographic photosensitive member increases, causing abnormal noise such as blade squeal and stick-slip, which may affect the image and result in image defects.

[0018] As a result of intensive research by the present inventors, it was found that in an electrophotographic device using an a-Si photoreceptor, when the following toner is used as the toner, the initial cleaning stability is improved and the occurrence of image defects can be suppressed. That is, the toner used in the present invention has toner particles, and the toner particles contain resin A having a unit represented by the above formula (1). The resin A is a crystalline resin, and the content ratio of the unit represented by the above formula (1) in the resin A is 30% by mass or more and 100% by mass or less with respect to the total mass of the resin A.

[0019] Although it is only a guess, the inventors believe that when a toner having the above-mentioned characteristics is present in the surface layer of an inorganic material, such as an a-Si photoreceptor, and in the blade nip area, even a very small amount of toner acts to significantly reduce frictional force, thereby improving cleaning stability. The reason for this is not clear, but the present inventors speculate as follows. That is, the present inventors speculate that when an external force is applied to the toner, the crystal structure composed of the unit represented by formula (1) of the resin A contained in the toner particles tends to cleave on the crystal plane or between crystals. In the cleaning process, in the nip between the cleaning blade and the a-Si photoconductor, the toner is rubbed against the a-SiC:H or aC:H on the surface of the a-Si photoconductor. At this time, the present inventors speculate that a large external force is applied to the toner, and the crystal structure composed of the unit represented by formula (1) of the resin A in the toner particles may cleave. The present inventors speculate that this reduces the friction between the cleaning blade and the electrophotographic photoconductor, thereby exerting the effect of improving the stability of cleaning.

[0020] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. [Electrophotographic device] An image forming method using an electrophotographic apparatus that uses an a-Si photoconductor will be described with reference to FIG. First, the electrophotographic photoreceptor 101 is rotated, and the surface of the electrophotographic photoreceptor 101 is uniformly charged by a charger 102. Thereafter, the surface of the electrophotographic photoreceptor 101 is irradiated with image exposure light by an image exposure means 103, and an electrostatic latent image is formed on the surface of the electrophotographic photoreceptor 101, and then developed using toner supplied by a developer 104. As a result, a toner image is formed on the surface of the electrophotographic photoreceptor 101. Then, this toner image is transferred to an intermediate transfer body 105, and secondarily transferred from the intermediate transfer body 105 to a transfer material (not shown), and the toner image is fixed to the transfer material by a fixing means (not shown).

[0021] Meanwhile, the toner remaining on the surface of the electrophotographic photoreceptor 101 onto which the toner image has been transferred is removed by a cleaner 106. The cleaner 106 has a rubbing roller 106a having an elastic sponge that rubs against the electrophotographic photoreceptor 101, and a cleaning blade 106b. Thereafter, the surface of the electrophotographic photoreceptor 101 is exposed to light by a pre-exposure device 107, thereby removing static electricity from the electrophotographic photoreceptor 101. By repeating this series of processes, continuous image formation is performed.

[0022] The rubbing roller 106a is disposed to rub the surface of the electrophotographic photosensitive member 101 with an elastic sponge, thereby actively removing discharge products generated by charging. Further, a cleaning blade 106b is disposed so as to come into contact with the electrophotographic photosensitive member 101 to remove residual toner. If the rubbing roller 106a is disposed upstream of the cleaning blade 106b, a part of the residual toner after transfer is also removed by the rubbing roller 106a. Therefore, from the viewpoint of supplying a lubricant to the cleaning blade 106b, such an arrangement is disadvantageous in terms of the stability of cleaning in the initial stage of use.

[0023] However, as a result of investigations by the present inventors, it has become clear that the effect of the present invention, i.e., the effect of improving cleaning stability, can be more effectively achieved by positioning the rubbing roller 106a upstream of the cleaning blade 106b. The reason for this is not clear, but is speculated as follows. That is, when the toner enters the rubbing portion between the rubbing roller 106a and the surface of the electrophotographic photosensitive member 101, the toner itself is also rubbed and receives an external force. It is speculated that this external force creates a state in which the effects of the resin particles and toner shell described below are more easily exerted, allowing the toner to reach the contact area between the cleaning blade 106b and the electrophotographic photosensitive member 101.

[0024] The electrophotographic apparatus according to the present invention may be provided with a process cartridge. In this case, the process cartridge integrally supports the electrophotographic photosensitive member 101 and at least one means selected from the group consisting of the charger 102, the developer 104, the pre-exposure unit 107, and the cleaner 106.

[0025] [Process cartridge] The process cartridge according to the present invention integrally supports an electrophotographic photosensitive member and at least one means selected from the group consisting of a charging means, a developing means, a discharging means, and a cleaning means, and is detachably mountable to the main body of an electrophotographic apparatus. For example, the process cartridge according to the present invention is a process cartridge which integrally supports an electrophotographic photosensitive member, a developing means having a toner, and a cleaning means, and is detachably mountable to the main body of an electrophotographic apparatus.

[0026] FIG. 4 shows an example of a schematic configuration of an electrophotographic apparatus equipped with a process cartridge having an electrophotographic photosensitive member. In FIG. 4, a cylindrical electrophotographic photoreceptor 401 is rotated around an axis 402 in the direction of the arrow at a predetermined peripheral speed. During the rotation process, the surface (periphery) of the electrophotographic photoreceptor 401 is positively or negatively charged by a charging means (primary charging means) 403. Next, the surface of the electrophotographic photoreceptor 401 is irradiated with exposure light (image exposure light) 404 output from an exposure means (image exposure means) (not shown). The exposure light 404 is intensity modulated in response to a time-series electric digital image signal of the target image information. Examples of the exposure means include slit exposure and laser beam scanning exposure. In this way, an electrostatic latent image corresponding to the target image information is formed on the surface of the electrophotographic photoreceptor 401.

[0027] The electrostatic latent image formed on the surface of the electrophotographic photoreceptor 401 is then developed (normal development or reversal development) with toner contained in the developing means 405 to form a toner image. The toner image formed on the surface of the electrophotographic photoreceptor 401 is transferred to a transfer material 407 by a transfer means 406. Here, when the transfer material 407 is paper, it is taken out from a paper feed unit (not shown) in synchronization with the rotation of the electrophotographic photoreceptor 401 and fed between the electrophotographic photoreceptor 401 and the transfer means 406. A bias voltage of a polarity opposite to that of the charge held by the toner is applied to the transfer means 406 from a bias power source (not shown). The transfer means 406 may also be an intermediate transfer type transfer means having a primary transfer member, an intermediate transfer member, and a secondary transfer member.

[0028] The transfer material 407 onto which the toner image has been transferred is separated from the surface of the electrophotographic photosensitive member 401, transported to a fixing means 408, and subjected to a toner image fixing process, whereby the transfer material 407 is printed out of the electrophotographic device as an image-formed product (print, copy). After the toner image is transferred, the surface of the electrophotographic photoreceptor 401 is cleaned by cleaning means 409 to remove any adhering matter such as residual toner. The residual toner can also be collected by developing means 405 or the like. Furthermore, if necessary, the surface of the electrophotographic photoreceptor 401 is subjected to a charge removal process by irradiation with pre-exposure light 410 from a pre-exposure means (not shown), and is then repeatedly used for image formation. Note that when the charging means 403 is a contact charging means using a roller-shaped charging member (hereinafter also referred to as a "charging roller"), the pre-exposure means is not necessarily required.

[0029] Among the components such as the electrophotographic photosensitive member 401, charging means 403, developing means 405, transfer means 406, and cleaning means 409, a plurality of elements are selected and housed in a container and supported integrally as a process cartridge. This process cartridge may be configured so as to be detachably attached to the main body of an electrophotographic apparatus such as a copying machine or a laser beam printer. In FIG. 4, the electrophotographic photosensitive member 401, charging means 403, developing means 405, and cleaning means 409 are supported integrally to form a cartridge. Then, a guide means 412 such as a rail of the main body of the electrophotographic apparatus is used to form a process cartridge 411 that is detachably attached to the main body of the electrophotographic apparatus.

[0030] [Electrophotographic photoreceptor] FIG. 2 is a schematic diagram showing an example of the layer structure of the a-Si photoreceptor used in the present invention. The photoreceptor 200 shown in FIG. 2 has a voltage-resistant layer 202 , a charge injection blocking layer 203 , a photoconductive layer 204 , and a surface protection layer 205 on a conductive substrate 201 . The voltage-resistant layer 202 is formed of hydrogenated amorphous silicon nitride (hereinafter also abbreviated as a-SiN:H), the charge injection blocking layer 203 and the photoconductive layer 204 are formed of a-Si:H, and the surface protection layer 205 is formed of a-SiC:H or aC:H.

[0031] Next, the conductive substrate and each layer constituting the photoreceptor having the above-mentioned layer structure will be described. (Conductive substrate) The material of the conductive substrate is preferably one that forms a Schottky junction with the voltage-resistant layer formed directly on the surface of the conductive substrate. When a-SiN:H is used as the material of the voltage-resistant layer, an alloy mainly composed of aluminum is a suitable material. The surface of the conductive substrate may be roughened. The surface roughness Sa of the conductive substrate after roughening may be, for example, 80 nm or more and 120 nm or less. This makes it possible to obtain an electrophotographic photoreceptor having an arithmetic mean roughness Sa of the surface of the electrophotographic photoreceptor of 80 nm or more and 120 nm or less, for example, when the electrophotographic photoreceptor is formed by a plasma CVD method. The surface of the conductive substrate may be roughened by, for example, wet blasting, sputter etching, gas etching, polishing, turning, wet etching, galvanic corrosion, etc. If the drawn pipe satisfies the above-mentioned surface roughness, it may be used as it is without surface treatment for adjusting the surface shape.

[0032] (Pressure-resistant layer) In the electrophotographic process, a voltage of the opposite polarity to the charge polarity of the photoconductor may be applied during the development process, transfer process, etc. The voltage-resistant layer is a layer that prevents the photoconductor from breaking down when a voltage of the opposite polarity to the charge polarity of the photoconductor is applied. The material of the voltage-resistant layer is made of a-SiN:H. With respect to the a-SiN:H constituting the voltage-resistant layer, there is no particular restriction on the ratio (N / (Si+N)) of the number of nitrogen atoms (N) to the sum of the number of silicon atoms (Si) and the number of nitrogen atoms (N). Specifically, the ratio (N / (Si+N)) is preferably 0.10 or more, and more preferably 0.15 or more and less than 0.30. By making (N / (Si+N)) less than 0.30, the N in the a-SiN:H acts as an electron donor. In other words, the a-SiN:H in this region can be seen as a-Si:H doped with N, and the voltage-blocking layer can be said to be n-type a-Si. It is known that dark conductivity is maximized when (N / (Si+N)) is approximately 0.25. In order for the a-SiN:H used in the voltage-resistant layer to function adequately as an N-doped a-Si:H, the (N / (Si+N)) value should preferably be in the range of 0.15 or more.

[0033] (charge injection blocking layer) The charge injection blocking layer has the function of blocking the injection of electrons from the conductive substrate side into the photoconductive layer when the surface of the photoreceptor is positively charged. The material of the charge injection blocking layer is based on the material constituting the photoconductive layer, and contains a relatively larger amount of atoms for controlling electron conductivity than the photoconductive layer. In the photoreceptor used in the present invention, atoms belonging to Group 13 of the periodic table are used as atoms contained in the charge injection blocking layer in order to control the electron conductivity. Among the atoms belonging to Group 13 of the periodic table, boron atoms (B), aluminum atoms (Al), and gallium atoms (Ga) are preferred. The content of atoms belonging to Group 13 of the periodic table contained in the charge injection blocking layer is 1×10 relative to the content of silicon atoms (Si) contained in the charge injection blocking layer. 2 ppm or more 3×10 3 It is preferably less than ppm.

[0034] The atoms belonging to Group 13 of the periodic table may be contained in the charge injection blocking layer in a uniform distribution state throughout, or may be contained in a non-uniform distribution state in the film thickness direction. In either case, it is preferable for the atoms for controlling the electron conductivity to be contained in the charge injection blocking layer in a uniform distribution in the in-plane direction parallel to the surface of the substrate in order to achieve uniform characteristics. Furthermore, by containing at least one type of atom selected from the group consisting of carbon atoms, nitrogen atoms and oxygen atoms in the charge injection blocking layer, the adhesion between the charge injection blocking layer and the voltage resistant layer can be improved.

[0035] (Photoconductive layer) The photoconductor used in the present invention uses a-Si:H as the material of the photoconductive layer, and hydrogen atoms and / or halogen atoms are contained in the a-Si:H to compensate for dangling bonds in the a-Si:H. The total number of hydrogen atoms (H) and halogen atoms (X) (H+X) is preferably 10 atomic % or more, more preferably 15 atomic % or more, relative to the total number of silicon atoms (Si), hydrogen atoms (H) and halogen atoms (X) (Si+H+X). Also, (H+X) is preferably 30 atomic % or less, more preferably 25 atomic % or less, relative to (Si+H+X).

[0036] In the present invention, it is preferable that the photoconductive layer contains atoms for controlling the electron conductivity as necessary. The atoms for controlling the electron conductivity may be contained in a state in which they are uniformly distributed throughout the photoconductive layer, or may be contained in a state in which they are non-uniformly distributed in the film thickness direction. Atoms for controlling the electron conductivity include so-called impurities in the semiconductor field. That is, atoms belonging to Group 13 of the periodic table that impart p-type conductivity or atoms belonging to Group 15 of the periodic table that impart n-type conductivity can be used. Among the atoms belonging to Group 13 of the periodic table, boron atoms (B), aluminum atoms (Al), and gallium atoms (Ga) are preferred. Among the atoms belonging to Group 15 of the periodic table, phosphorus atoms (P) and arsenic atoms (As) are preferred. The content of atoms for controlling the electron conductivity contained in the photoconductive layer is 1×10 -2 It is preferably at least 1 x 10 atomic ppm, while it is preferably at most 1 x 10 atomic ppm. The photoconductive layer may be composed of a single layer, or may be composed of a plurality of layers (for example, a charge generating layer and a charge transporting layer).

[0037] (Surface protective layer) The surface protection layer is made of a-SiC:H or aC:H from the viewpoint of durability. In the positively charged photoreceptor having the above-mentioned layer structure, the surface protective layer also has a charge injection blocking function for preventing holes, which are the charging charges, from being injected into the photoconductive layer. When the surface protective layer is made of a-SiC:H, the ratio C / (Si+C) of the number of carbon atoms (C) to the sum of the number of silicon atoms (Si) and the number of carbon atoms (C) is preferably in the range of 0.50 or more. It is known that the optical band gap of a-SiC:H becomes large when C / (Si+C) is about 0.60, which is effective in efficiently transmitting the exposure light to the photoconductive layer. On the other hand, if C / (Si+C) is increased, the surface protective layer tends to be less prone to oxidation.

[0038] The surface protective layer may have a multi-layer structure, and in this case, it is preferable that the surface protective layer has a first region, a second region, and a third region from the photoconductive layer side. In the first region, the C / (Si+C) can be changed stepwise or continuously to suppress the reflection of light at the interface between the photoconductive layer and the surface protective layer. In the second region, in order to increase the transmittance of the exposure light, C / (Si+C) is preferably 0.50 or more and 0.80 or less. Since the third region becomes the outermost surface, it is preferable that C / (Si+C) is 0.90 or more in order to suppress oxidation of the surface. The third region also has a significant effect on cleaning characteristics.

[0039] As a result of the inventors' investigations, it has become clear that the effect of the present invention, which improves cleaning stability, can be more effectively achieved by adjusting the C / (Si+C) of the surface of the electrophotographic photosensitive member to 0.95 or more and 0.99 or less.

[0040] The reason for this is not clear, but it is speculated that the specific action of the long-chain alkyl moiety contained in the resin A of the toner described above may have some relationship to the amount of Si atoms on the surface. That is, as the amount of Si increases, not only the number of C—C bonds and Si—C bonds but also the number of Si—O bonds on the outermost surface also increases. The present inventors speculate that when there are many Si-O bonds, the effect of reducing frictional force due to the sliding of the long-chain alkyl moieties described above is less likely to be exhibited.

[0041] In addition, in the aC:H system, which does not contain Si, it is practically difficult to make all C atoms sp3 bonds, and the structure also contains sp2 bonds. We believe that this is related to the effect of friction. In other words, the inventors speculate that the inclusion of a small amount of Si may be preferable in order to make the film more structurally stable and to obtain a greater effect in reducing the frictional force caused by rubbing against the long-chain alkyl moieties.

[0042] Furthermore, when the surface protective layer is formed of either a-SiC:H or aC:H, hydrogen atoms and / or halogen atoms are contained to compensate for dangling bonds, similar to the a-Si:H used in the photoconductive layer. The total number of hydrogen atoms (H) and halogen atoms (X) (H+X) is preferably 20 atomic % or more and 50 atomic % or less of the total number of silicon atoms (Si), carbon atoms (C), hydrogen atoms (H) and halogen atoms (X) (Si+C+H+X), and more preferably 30 atomic % or more and 40 atomic % or less.

[0043] (Manufacturing method of a-Si photoconductor) The manufacturing method of the a-Si photoreceptor may be any method that can form a layer that satisfies the above-mentioned specifications. Specifically, the method includes a plasma CVD method, a vacuum deposition method, a sputtering method, an ion plating method, etc. Among these, the plasma CVD method is preferable in terms of ease of supplying raw materials, etc.

[0044] A manufacturing apparatus and a manufacturing method using the plasma CVD method will be described below. FIG. 3 is a schematic diagram showing an example of a deposition apparatus for an electrophotographic photosensitive member by an RF plasma CVD method using a high-frequency power source, which can be used for producing an a-Si photosensitive member according to the present invention. This deposition apparatus is roughly composed of a deposition apparatus 3100 having a reaction vessel 3110 , a source gas supplying apparatus 3200 , and an exhaust apparatus (not shown) for reducing the pressure inside the reaction vessel 3110 . A substrate 3112 connected to earth, a heater 3113 for heating the substrate, and a source gas introduction pipe 3114 are installed in a reaction vessel 3110 in a deposition apparatus 3100. Furthermore, a high frequency power supply 3120 is connected to the cathode electrode 3111 via a high frequency matching box 3115. The raw material gas supplying device 3200 is composed of raw material gas cylinders 3221-3227, valves 3231-3237, pressure regulators 3261-3267, inlet valves 3241-3247, and outlet valves 3251-3257. It further includes mass flow controllers 3211-3217. The gas cylinders in which the respective raw material gases are sealed are connected to a raw material gas introduction pipe 3114 in the reaction vessel 3110 via an auxiliary valve 3260. 3116 is a gas pipe, 3117 is a leak valve, and 3121 is an insulating material.

[0045] Next, a method for forming a deposited film using this apparatus will be described. First, the substrate 3112, which has been degreased and washed in advance, is placed in the reaction vessel 3110 via the receiving stand 3123. Next, an exhaust device (not shown) is operated to exhaust the inside of the reaction vessel 3110. While watching the display of the vacuum gauge 3119, when the pressure inside the reaction vessel 3110 reaches a predetermined pressure, for example, 1 Pa or less, power is supplied to the heater 3113 for heating the substrate, and the substrate 3112 is heated to a predetermined temperature, for example, 50 to 350° C. At this time, an inert gas such as Ar or He can be supplied to the reaction vessel 3110 from the raw material gas supply device 3200 to perform heating in an inert gas atmosphere.

[0046] Next, the gas used for forming the deposited film is supplied to the reaction vessel 3110 from the source gas supply device 3200. That is, the valves 3231-3237, the inlet valves 3241-3247, and the outlet valves 3251-3257 are opened as necessary, and the flow rates are set in the mass flow controllers 3211-3217. When the flow rates of the mass flow controllers are stabilized, the main valve 3118 is operated while watching the display of the vacuum gauge 3119, and the pressure in the reaction vessel 3110 is adjusted to the desired pressure. When the desired pressure is obtained, high frequency power is applied from the high frequency power supply 3120, and at the same time, the high frequency matching box 3115 is operated to generate plasma discharge in the reaction vessel 3110. After that, the high frequency power is quickly adjusted to the desired power to form the deposited film.

[0047] When the formation of a predetermined deposition film is completed, the application of high frequency power is stopped, and the valves 3231-3237, the inlet valves 3241-3247, the outlet valves 3251-3257, and the auxiliary valve 3260 are closed to terminate the supply of the source gas. At the same time, the main valve 3118 is fully opened, and the inside of the reaction vessel 3110 is evacuated to a pressure of 1 Pa or less. This completes the formation of the deposition film, but when forming multiple deposition films, the above procedure can be repeated to form each layer. The flow rate of the raw material gas, pressure, etc. can also be changed over a certain period of time in accordance with the conditions for forming the photoconductive layer to form the junction region.

[0048] After all the deposition films have been formed, the main valve 3118 is closed, an inert gas is introduced into the reaction vessel 3110 to return the pressure to atmospheric pressure, and the substrate 3112 is then removed. In forming the pressure-resistant layer, the source gas for supplying silicon atoms may be, for example, silanes such as silane (SiH4) or disilane (Si2H6). The source gas for supplying nitrogen atoms may be, for example, ammonia (NH3) or nitrogen (N2). The source gas for supplying oxygen atoms may be, for example, oxygen (O2) or nitric oxide (NO) in addition to the above-mentioned source gases. The source gas for supplying hydrogen atoms may be, for example, hydrogen (H2) in addition to the above-mentioned source gases. When carbon atoms or the like are contained in the pressure-resistant layer in order to improve adhesion with the conductive substrate, a gaseous or easily gasifiable substance containing the atoms to be contained may be appropriately used as a material.

[0049] In forming the charge injection blocking layer, as described above, silanes such as silane (SiH4) and disilane (Si2H6) can be suitably used as the source gas for supplying silicon atoms. Furthermore, diborane (B2H6) can be suitably used as the source gas for supplying group 13 atoms. Furthermore, in addition to the above source gases, hydrogen (H2) can also be suitably used as the source gas for supplying hydrogen atoms. Furthermore, when carbon atoms, oxygen atoms, nitrogen atoms, etc. are contained in the charge injection blocking layer in order to improve adhesion with the pressure-resistant layer, a gaseous or easily gasifiable substance containing each atom may be appropriately used as a material.

[0050] In forming the photoconductive layer, as the raw material gas for supplying silicon atoms, silanes such as silane (SiH4) and disilane (Si2H6) can be suitably used as the raw material gas for supplying hydrogen atoms, in addition to the above-mentioned silanes, for example, hydrogen (H2) can also be suitably used as the raw material gas for supplying hydrogen atoms. In addition, when the photoconductive layer contains the above-mentioned halogen atoms, atoms for controlling the conductivity of electrons, carbon atoms, oxygen atoms, nitrogen atoms, etc., a gaseous or easily gasifiable substance containing each atom may be appropriately used as a material.

[0051] When a-SiC:H is formed as the surface protective layer, silanes such as silane (SiH4) and disilane (Si2H6) can be preferably used as the source gas for supplying silicon atoms, as described above. Also, gases such as methane (CH4) and acetylene (C2H2) can be preferably used as the source gas for supplying carbon atoms. By adjusting the mixture ratio of these source gases, the C / (Si+C) of a-SiC:H can be adjusted. On the other hand, when aC is formed as the surface protective layer, gases such as methane (CH4) and acetylene (C2H2) can be preferably used as the source gas for supplying carbon atoms, as described above. Also, for either material, hydrogen (H2) can be preferably used as the source gas for supplying hydrogen atoms.

[0052] [toner] <Binding resin> The toner used in the electrophotographic device according to the present invention has toner particles, and the toner particles contain, as a binder resin, resin A having a unit represented by the following formula (1). Furthermore, resin A is a crystalline resin, and the content ratio of the unit represented by the following formula (1) in resin A is 30% by mass or more and 100% by mass or less with respect to the total mass of resin A. [ka] (In formula (1), R 11 represents a hydrogen atom or a methyl group, and R 12 represents an alkyl group having 18 to 36 carbon atoms. Resin A may be a vinyl resin, or a hybrid resin in which a resin other than a vinyl resin is bonded to the unit represented by formula (1). When resin A is a vinyl resin, the vinyl resin constituting resin A may be a random copolymer or a block copolymer of polymerizable monomers forming each unit. From the viewpoint of low-temperature fixability and ease of control of other properties, resin A is preferably a vinyl resin. In the present invention, resin A is a crystalline resin and has a melting point. That is, a crystalline resin refers to a resin in which an endothermic peak is observed in differential scanning calorimetry (DSC), for example.

[0053] The unit represented by formula (1) has R 12 R has an alkyl group having 18 to 36 carbon atoms, which gives the resin A crystallinity. 12 When the number of carbon atoms in the alkyl group represented by R is 18 or more and 36 or less, the effect of improving the cleaning stability described above can be obtained. 12 When the alkyl group represented by R has 18 or more carbon atoms, the resin A has sufficient crystallinity and can exhibit the effect of improving the cleaning stability. 12 If the number of carbon atoms in the alkyl group represented by R is 36 or less, the resin A not only has crystallinity but also has 12 The number of carbon atoms in the alkyl group represented by the formula (I) is not too large, and the above-mentioned crystal cleavage is likely to occur. This makes it possible to exert the effect of improving the stability of cleaning.

[0054] When the content of the unit represented by formula (1) in resin A is 30 mass % or more and 100 mass % or less relative to the total mass of resin A, cleaning stability is improved. When resin A contains units other than the unit represented by formula (1) described later, the content of the unit represented by formula (1) in resin A is preferably 30 mass % or more and 90 mass % or less, and more preferably 30 mass % or more and 80 mass % or less, based on the total mass of resin A.

[0055] The unit represented by formula (1) is preferably a unit derived from at least one (first polymerizable monomer) selected from the group consisting of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms. In this specification, the term "(meth)acrylic acid" refers to a compound of acrylic acid or methacrylic acid. That is, for example, "(meth)acrylic acid ester" refers to an acrylic acid ester or a methacrylic acid ester.

[0056] Examples of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms include (meth)acrylic acid esters having a straight-chain alkyl group having 18 to 36 carbon atoms [stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosanyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, ceryl (meth)acrylate, octacosyl (meth)acrylate, myrisyl (meth)acrylate, dotriacontyl (meth)acrylate, etc.] and (meth)acrylic acid esters having a branched alkyl group having 18 to 36 carbon atoms [2-decyltetradecyl (meth)acrylate, etc.].

[0057] Of these, from the viewpoint of low-temperature fixability of the toner, the unit represented by formula (1) is preferably a unit derived from at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having a carbon number of 18 to 36. More preferably, the unit represented by formula (1) is a unit derived from at least one selected from the group consisting of linear stearyl (meth)acrylate and behenyl (meth)acrylate. The unit represented by formula (1) may be used alone or in combination of two or more. The melting point of resin A is preferably 45°C or higher and 90°C or lower, and more preferably 50°C or higher and 85°C or lower.

[0058] Resin A may contain units other than the unit represented by the above formula (1). When the resin A is a vinyl resin, examples of the polymerizable monomer that forms a unit other than the unit represented by formula (1) include the following.

[0059] Monomers having a nitrile group; for example, acrylonitrile, methacrylonitrile, etc. Monomers having a hydroxy group; for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and the like. Monomers having an amide group: for example, acrylamide, monomers obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having 2 to 30 carbon atoms and an ethylenically unsaturated bond (such as acrylic acid and methacrylic acid) by a known method, etc. Monomer having a urea group: for example, a monomer obtained by reacting an amine having 3 to 22 carbon atoms [primary amine (normal butylamine, t-butylamine, propylamine, isopropylamine, etc.), secondary amine (di-normal ethylamine, di-normal propylamine, di-normal butylamine, etc.), aniline, cycloxylamine, etc.] with an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond by a known method, etc. Monomers having a carboxy group; for example, methacrylic acid, acrylic acid, 2-carboxyethyl (meth)acrylate, etc.

[0060] Vinyl esters; for example, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate, and vinyl octoate. (Meth)acrylic acid esters: for example, styrene, o-methylstyrene and other styrene derivatives thereof, methyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and the like. Unsaturated polyenes; for example, unsaturated monoolefins such as ethylene, propylene, butylene, isobutylene; butadiene, isoprene, and the like. Aromatic divinyl compounds; for example, divinylbenzene, divinylnaphthalene, etc. Diacrylate compounds linked by alkyl chains; for example, ethylene glycol diacrylate, 1,3-butylene glycol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, and the above compounds in which the acrylate is replaced with a methacrylate. Other examples include diacrylate compounds linked by alkyl chains containing ether bonds; diacrylate compounds linked by chains containing aromatic groups and ether bonds; polyester-type diacrylates; and polyfunctional crosslinking agents.

[0061] The polymerizable monomers forming units other than the unit represented by formula (1) may be used alone or in combination of two or more.

[0062] When the resin A is a vinyl resin, it can be produced using the exemplified polymerizable monomer and polymerization initiator. From the viewpoint of efficiency, it is preferable to use 0.05 parts by mass or more and 10 parts by mass or less of the polymerization initiator with respect to 100 parts by mass of the polymerizable monomer.

[0063] Examples of the polymerization initiator include the following. 2,2'-Azobisisobutyronitrile, 2,2'-Azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-Azobis(2,4-dimethylvaleronitrile), 2,2'-Azobis(2-methylbutyronitrile), Dimethyl-2,2'-azobisisobutyrate, 1,1'-Azobis(1-cyclohexanecarbonitrile), 2-Carbamoylazoisobutyronitrile, 2,2'-Azobis(2,4,4-trimethylpentane), 2-Phenylazo-2,4-dimethyl-4-methoxyvaleronitrile, 2,2'-Azobis(2-methylpropane), Methyl ethyl ketone peroxide, Acetone Ketone peroxides such as ethyl acetone peroxide and cyclohexanone peroxide, 2,2-bis(tert-butylperoxy)butane, tert-butyl hydroperoxide, cumene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, di-tert-butyl peroxide, tert-butylcumyl peroxide, dicumyl peroxide, α,α'-bis(tert-butylperoxyisopropyl)benzene, isobutyl peroxide, octanoyl peroxide, decanoyl peroxide, lauroyl peroxide, 3,5,5-Trimethylhexanoyl peroxide, benzoyl peroxide, m-trioyl peroxide, diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di-2-ethoxyethyl peroxycarbonate, dimethoxyisopropyl peroxydicarbonate, di(3-methyl-3-methoxybutyl) peroxycarbonate, acetylcyclohexylsulfonyl peroxide, tert-butyl peroxyacetate, tert-butyl peroxy diisobutyrate, tert-butyl peroxy neodecanoate, tert-butyl peroxy 2-ethylhexanoate, tert-butyl peroxy laurate, tert-butyl peroxy benzoate, tert-butyl peroxy isopropyl carbonate, di-tert-butyl peroxy isophthalate, tert-butyl peroxy allyl carbonate, tert-amyl peroxy 2-ethylhexanoate, di-tert-butyl peroxy hexahydroterephthalate, di-tert-butyl peroxy azelate.

[0064] Resin A may also be a hybrid resin in which a resin other than a vinyl resin is bonded to a unit represented by formula (1). In this case, examples of the resin other than the vinyl resin that can be used include silicone resin, polyester resin, polyurethane, polyamide resin, furan resin, epoxy resin, xylene resin, polyvinyl butyral, terpene resin, coumarone-indene resin, and petroleum-based resin.

[0065] Among these, from the viewpoints of low-temperature fixing property and charge control, it is preferable to use a polyester resin as the resin other than the vinyl resin. The polyester resin may be either an amorphous polyester resin or a crystalline polyester resin, but an amorphous polyester is more preferable.

[0066] The polyester resin may be a resin having a "polyester unit" in the resin chain. Specific examples of components constituting the polyester unit include divalent or higher alcohol monomer components and divalent or higher carboxylic acid monomer components, divalent or higher carboxylic acid anhydrides, divalent or higher carboxylic acid esters, and the like.

[0067] For example, examples of dihydric or higher alcohol monomer components include alkylene oxide adducts of bisphenol A such as polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, and polyoxypropylene(6)-2,2-bis(4-hydroxyphenyl)propane; ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, 1,4-butenediol, 1,5-pentanediol, and 1,6-hexanediol. Examples of suitable glycerol include 1,4-butadiene glycol, trimethylene glycol, tetramethylene glycol, pentamethylene glycol, hexamethylene glycol, octamethylene glycol, nonamethylene glycol, decamethylene glycol, neopentyl glycol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerin, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene.

[0068] Among these, aromatic diols can be preferably used as the alcohol monomer component. In the alcohol monomer component constituting the polyester resin, the aromatic diol is preferably contained in a ratio of 80 mol % or more based on the total mole number of the alcohol monomer component.

[0069] On the other hand, examples of acid monomer components such as divalent or higher carboxylic acids, divalent or higher carboxylic acid anhydrides, and divalent or higher carboxylic acid esters include aromatic dicarboxylic acids or anhydrides such as phthalic acid, isophthalic acid, and terephthalic acid; alkyl dicarboxylic acids or anhydrides such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, glutaconic acid, azelaic acid, sebacic acid, nonanedicarboxylic acid, decanedicarboxylic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, maleic acid, fumaric acid, mesaconic acid, citraconic acid, and itaconic acid; succinic acid or anhydrides substituted with an alkyl group or alkenyl group having 6 to 18 carbon atoms; and unsaturated dicarboxylic acids or anhydrides such as fumaric acid, maleic acid, and citraconic acid.

[0070] Of these, as the acid monomer component, polyvalent carboxylic acids such as terephthalic acid, succinic acid, adipic acid, fumaric acid, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and anhydrides thereof can be preferably used. A preferred method for obtaining a hybrid resin is to carry out a polymerization reaction of either or both of the vinyl resin or vinyl copolymer unit, and the polyester resin in the presence of a polymer containing a monomer component capable of reacting with each of the vinyl resin and the vinyl copolymer unit, and the polyester resin. The content of resin A in the toner particles is preferably 40% by mass or more relative to the total mass of the toner particles, since the above-mentioned effect of low-temperature fixability is easily obtained. More preferably, it is 50% by mass or more. There is no particular upper limit, but considering the contents of colorant and release agent contained in the toner particles, it is preferably 90% by mass or less.

[0071] In the present invention, the binder resin contained in the toner particles may contain a resin other than the resin A as necessary for the purpose of improving pigment dispersibility, etc., to the extent that the effect of the present disclosure is not impaired. Resins other than Resin A include the following. Polyvinyl chloride, phenolic resin, natural resin modified phenolic resin, natural resin modified maleic acid resin, polyvinyl acetate, silicone resin, polyester resin, polyurethane resin, polyamide resin, furan resin, epoxy resin, xylene resin, polyvinyl butyral, terpene resin, coumarone-indene resin, petroleum-based resin. The content of the resin other than the resin A in the toner particles is preferably 0% by mass or more and 30% by mass or less with respect to the total mass of the toner particles.

[0072] <Release agent> The toner particles may contain a wax as a release agent. Examples of such wax include the following: Hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or their block copolymers; waxes whose main component is fatty acid esters such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax. Saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and valinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene bi saturated fatty acid bisamides such as stearic acid amide; unsaturated fatty acid amides such as ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, and N,N'-dioleyl sebacic acid amide; aromatic bisamides such as m-xylene bisstearic acid amide and N,N'-distearyl isophthalic acid amide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having hydroxyl groups obtained by hydrogenating vegetable oils and fats.

[0073] Among these waxes, from the viewpoint of improving low-temperature fixing property and fixing separation property, preferred are hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax, and fatty acid ester waxes such as carnauba wax, and more preferred are hydrocarbon waxes from the viewpoint of further improving hot offset resistance. The content of the wax is preferably 3 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the binder resin.

[0074] <Coloring agent> The toner particles may contain a colorant, if necessary. Examples of the colorant include the following. Examples of black colorants include carbon black, and those toned to black using a yellow colorant, a magenta colorant, and a cyan colorant. As the colorant, a pigment may be used alone, or a dye and a pigment may be used in combination. From the viewpoint of the image quality of a full-color image, it is preferable to use a dye and a pigment in combination.

[0075] Magenta toner pigments include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35. Dyes for magenta toners include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.

[0076] Pigments for cyan toners include the following: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45; copper phthalocyanine pigments having 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton. Dyes for cyan toners include CI Solvent Blue 70.

[0077] Yellow toner pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20. Yellow toner dyes include CI Solvent Yellow 162.

[0078] These colorants can be used alone or in combination, or in the form of a solid solution. The colorant is selected in consideration of hue angle, chroma, brightness, light resistance, transparency on an OHP sheet, and dispersibility in a toner. The content of the colorant is preferably 0.1 parts by mass or more and 30.0 parts by mass or less per 100 parts by mass of the binder resin.

[0079] <Charge control agent> The toner may contain a charge control agent as necessary. By blending a charge control agent, the charge characteristics can be stabilized and the amount of triboelectric charge can be optimally controlled according to the development system. Any known charge control agent can be used, but it is preferable to use a positive charge control agent, particularly when used in combination with the photoreceptor used in the present invention. Positive charge control agents include azine compounds, azine dyes, nigrosine dyes, quaternary ammonium salts, resins containing quaternary ammonium cationic groups, triaminotriphenylmethane compounds and imidazole compounds. The charge control agent may be added internally or externally to the toner particles. The content of the charge control agent is preferably 0.2 parts by mass to 10.0 parts by mass, more preferably 0.5 parts by mass to 10.0 parts by mass, based on 100 parts by mass of the binder resin.

[0080] <Inorganic fine particles> The toner may contain inorganic fine particles as necessary. The inorganic fine particles may be added internally to the toner particles, or may be mixed with the toner particles as an external additive. Examples of inorganic fine particles include silica fine particles, titanium oxide fine particles, alumina fine particles, and double oxide fine particles thereof. Among inorganic fine particles, silica fine particles and titanium oxide fine particles are preferred for improving flowability and uniform charging. The inorganic fine particles are preferably hydrophobized with a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof.

[0081] From the viewpoint of improving fluidity, inorganic fine particles as external additives should have a specific surface area of ​​50 m 2 / g~400m 2 From the viewpoint of improving durability and stability, it is preferable that the inorganic fine particles as the external additive have a specific surface area of ​​10 m 2 / g~50m 2In order to achieve both improved fluidity and durability and stability, it is preferable that the specific surface area is 50 m 2 / g~400m 2 / g and inorganic fine particles with a specific surface area of ​​10m 2 / g~50m 2 / g of inorganic fine particles may be used in combination. The content of the inorganic fine particles is preferably 0.1 parts by mass to 10.0 parts by mass with respect to 100 parts by mass of the toner particles. When the inorganic fine particles are used as an external additive, a known mixer such as a Henschel mixer can be used to mix the toner particles and the inorganic fine particles as the external additive.

[0082] <Resin particles> The toner particles preferably have resin particles on the surface. The resin particles are provided on the surface of the toner particles as external additive particles, and function as, for example, spacer particles. The resin particles are particles mainly composed of resin. The resin particles preferably contain a styrene-acrylic acid resin. The content of the styrene-acrylic acid resin in the resin particles is preferably more than 70% by mass, more preferably 95% by mass or more, and even more preferably 100% by mass, based on the total mass of the resin particles.

[0083] The styrene-acrylic acid resin is a resin having a repeating unit derived from a styrene monomer and a repeating unit derived from an acrylic acid monomer.

[0084] Examples of styrene-based monomers include styrene, alkylstyrenes (more specifically, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, ethylstyrene, 2,3-dimethylstyrene, 2,4-dimethylstyrene, o-tert-butylstyrene, m-tert-butylstyrene, and p-tert-butylstyrene, etc.), and halogenated styrenes (more specifically, α-chlorostyrene, o-chlorostyrene, m-chlorostyrene, and p-chlorostyrene, etc.). The content ratio of the repeating unit derived from the styrene-based monomer in the styrene-acrylic acid resin is preferably 3 mol% to 70 mol%, more preferably 5 mol% to 25 mol%, based on the total number of moles of the styrene-acrylic acid resin. By setting the content ratio of the repeating unit derived from the styrene-based monomer to 3 mol% to 70 mol%, it is possible to impart appropriate hydrophobicity to the resin particles, and as a result, it is possible to suppress the embedding of the resin particles in the toner particles.

[0085] Examples of the acrylic acid monomer include (meth)acrylic acid, (meth)acrylonitrile, and (meth)acrylic acid alkyl esters (particularly, (meth)acrylic acid alkyl esters having an alkyl group with 1 to 4 carbon atoms in the ester moiety). Examples of the (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, iso-propyl (meth)acrylate, butyl (meth)acrylate (n-butyl (meth)acrylate), iso-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Examples of the acrylic acid monomer include (meth)acrylic acid alkyl esters, and more preferably butyl (meth)acrylate.

[0086] The content of repeating units derived from acrylic acid monomers in the styrene-acrylic acid resin is preferably 20 mol % or more and 95 mol % or less, and more preferably 30 mol % or more and 60 mol % or less, based on the total mass of the styrene-acrylic acid resin.

[0087] The styrene-acrylic acid resin is preferably crosslinked. In this manner, the styrene-acrylic acid resin contained in the resin particles is crosslinked, which gives the resin particles appropriate rigidity and makes it easier for the resin particles to function as spacers. Examples of crosslinked styrene-acrylic acid resins include styrene-acrylic acid resins having repeating units derived from a monomer (hereinafter sometimes referred to as a crosslinkable monomer) having two or more crosslinkable groups (e.g., a vinyl group and a (meth)acryloyl group). Examples of crosslinkable monomers include divinylbenzene, ethylene glycol diacrylic acid, ethylene glycol dimethacrylic acid, polyethylene glycol diacrylic acid, polyethylene glycol dimethacrylic acid, trimethylolpropane triacrylic acid, and trimethylolpropane trimethacrylic acid, with divinylbenzene being preferred.

[0088] When the styrene-acrylic acid resin has a repeating unit derived from a crosslinkable monomer, the content ratio of the repeating unit derived from the crosslinkable monomer in the styrene-acrylic acid resin preferably satisfies the following: That is, the content ratio of the repeating unit derived from the crosslinkable monomer relative to the total mass of the styrene-acrylic acid resin is preferably 20 mol % or more and 80 mol % or less, and more preferably 40 mol % or more and 60 mol % or less.

[0089] The resin particles preferably contain a copolymer having a unit represented by the following formula (2) and a unit represented by the following formula (3). [ka] (In formula (2), R 21 represents a hydrogen atom or a methyl group, and R 22 represents an alkyl group having 1 to 4 carbon atoms.

[0090] The total content of the unit represented by formula (2) and the unit represented by formula (3) in the resin particles is preferably more than 70 mass % and not more than 100 mass % based on the total mass of the resin particles. In addition, the total content of the unit represented by formula (2) and the unit represented by formula (3) in the copolymer is preferably 90% by mass or more and 100% by mass or less, based on the total mass of the copolymer. In particular, the resin particles are preferably made of a resin derived from styrene and butyl methacrylate, or a resin derived from styrene, butyl methacrylate, and divinylbenzene.

[0091] The number-average primary particle diameter of the resin particles is preferably 30 nm or more and 150 nm or less, and more preferably 50 nm or more and 80 nm or less. By making the number-average primary particle diameter of the resin particles 30 nm or more, a spacer effect can be exhibited. By making the number-average primary particle diameter of the resin particles 150 nm or less, detachment of the resin particles from the toner particles can be suppressed.

[0092] Furthermore, as a result of the investigations conducted by the present inventors, it has become clear that the effect of the present invention, that is, improved cleaning stability, can be more effectively exhibited by providing the above-mentioned resin particles on the surfaces of the toner particles. The reason for this is not clear, but is speculated as follows. That is, when toner particles having the above-mentioned resin particles on their surfaces are used, the toner particles approaching the blade nip portion receive a force from the cleaning blade, which causes some of the resin particles to separate from the toner particles. If resin particles separated from toner particles are present near such a nip portion, the toner particles can easily enter the nip portion, and the present inventors speculate that the resin particles thus play a role in assisting the opportunity for the long-chain alkyl moiety in the toner particles to rub against the photoreceptor surface. In order to obtain such an effect due to the resin particles, the number average primary particle size of the resin particles is preferably 30 nm or more and 150 nm or less.

[0093] <Toner shell> The toner particles may be configured to have a core (hereinafter also referred to as a toner core) containing the above-mentioned resin A and a shell (hereinafter also referred to as a toner shell) covering the core, as necessary. The shell preferably contains a resin having an amide bond and an ester bond.

[0094] The toner shell is composed of, for example, a resin, and it is preferable that the resin constituting the toner shell contains a polymer of a monomer including a compound represented by the following formula (5) (hereinafter also abbreviated as compound (5)). [ka] (In formula (5), R 51 represents a hydrogen atom or an alkyl group which may be substituted with a substituent.

[0095] In formula (5), R 51 Examples of the alkyl group represented by R include a methyl group, an ethyl group, and an isopropyl group. 51 When R represents an alkyl group substituted with a substituent, an example of the substituent on the alkyl group is a phenyl group. 51 Suitable examples of include a hydrogen atom, a methyl group, an ethyl group, and an isopropyl group.

[0096] The polymer of the monomer containing at least the compound (5) may be a polymer obtained by copolymerizing the compound (5) with another vinyl compound. The vinyl compound is a compound having a vinyl group (CH2=CH-) or a group in which hydrogen in the vinyl group is substituted. More specifically, examples of the vinyl compound include ethylene, propylene, butadiene, vinyl chloride, (meth)acrylic acid, methyl (meth)acrylate, (meth)acrylonitrile, and styrene. The vinyl compound can be addition polymerized by the carbon-carbon double bond (C=C) contained in the vinyl group or the like to become a polymer (resin).

[0097] As the other vinyl compound, one or more vinyl compounds selected from the group consisting of acrylic acid alkyl ester monomers and styrene monomers are preferred. Compound (5) forms a repeating unit represented by the following formula (5-1) (hereinafter also abbreviated as repeating unit (5-1)) by addition polymerization. 51 is R in Eq. (5). 51 is synonymous with. [ka]

[0098] The repeating unit (5-1) has an unopened oxazoline group. The unopened oxazoline group has a cyclic structure and exhibits strong positive charging. The unopened oxazoline group easily reacts with a carboxyl group, an aromatic sulfanyl group, and an aromatic hydroxyl group. For example, when the repeating unit (5-1) in the toner shell reacts with the carboxyl group of the polyester resin in the toner core, the oxazoline group opens and an amide bond and an ester bond are formed as shown in the following formula (5-2). The formation of such bonds strengthens the bond between the toner core and the toner shell, and prevents the toner shell from detaching from the toner core. 51 is R in formula (1). 51 In the following formula (5-2), * represents a site for bonding to an atom in the polyester resin contained in the toner core. [ka]

[0099] In order to suppress detachment of the toner shell from the toner core while increasing the positive chargeability of the toner, the toner shell preferably contains a vinyl resin having a repeating unit (5-1) and a repeating unit represented by formula (5-2) (hereinafter also abbreviated as repeating unit (5-2)). Hereinafter, the vinyl resin having the repeating unit (5-1) and the repeating unit (5-2) may be referred to as a specific vinyl resin. As the proportion (molar ratio) of the repeating unit (5-1) in the specific vinyl resin increases, the positive chargeability of the specific vinyl resin increases, which tends to increase the positive chargeability of the toner.

[0100] On the other hand, the higher the proportion (molar ratio) of the repeating unit (5-2) in the specific vinyl resin, the stronger the bond between the toner core and the toner shell tends to be. In order to enhance the positive chargeability and to further suppress the detachment of the toner shell from the toner core, it is preferable that the toner shell is composed only of the specific vinyl resin. The molar ratio of the repeating unit (5-1) to the repeating unit (5-2) in the specific vinyl resin can be adjusted, for example, by changing the acid value of the resin constituting the toner shell.

[0101] Furthermore, as a result of the investigations conducted by the present inventors, it has become clear that the effect of the present invention, that is, improved cleaning stability, can be more effectively exhibited by providing the above-mentioned toner shell on the surface of the toner particles. The reason for this is not clear, but is speculated as follows. That is, when toner particles having the above-mentioned toner shell on their surface are used, the toner particles approaching the blade nip portion are subjected to a force from the cleaning blade, which breaks a part of the toner shell and separates it from the toner core. When a part of the toner shell is separated from the toner core near such a nip, the toner core can easily enter the nip, and it is speculated that the toner shell assists the long-chain alkyl moiety in the toner core to rub against the photoreceptor surface. In order to obtain such an effect due to the toner shell, the thickness of the shell is preferably 30 nm or more and 60 nm or less.

[0102] [Developer] The toner can be used as a one-component developer, but in order to further improve dot reproducibility and provide stable images over a long period of time, it is preferable to mix the toner with a magnetic carrier and use it as a two-component developer. As the magnetic carrier, generally known carriers can be used, such as iron oxide; metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, chromium, and rare earth elements, alloy particles thereof, and oxide particles thereof; magnetic materials such as ferrite; magnetic material-dispersed resin carriers (so-called resin carriers) containing a magnetic material and a binder resin that holds the magnetic material in a dispersed state; and the like. When the toner is mixed with a magnetic carrier and used as a two-component developer, the concentration of the toner in the two-component developer is preferably 2% by mass or more and 15% by mass or less, and more preferably 4% by mass or more and 13% by mass or less, based on the total mass of the two-component developer.

[0103] [Toner manufacturing method] The toner used in the present invention may be produced by any known method, such as a pulverization method, a suspension polymerization method, a dissolution suspension method, an emulsion aggregation method, or a dispersion polymerization method, without any particular limitation. EXAMPLES

[0104] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Note that the number of parts in the following formulations is always based on mass unless otherwise specified.

[0105] [Production Examples of Electrophotographic Photoreceptors 1 to 9] An aluminum alloy tube (outer diameter: 84 mm, length: 370 mm) was prepared as a cylindrical conductive substrate. The outer peripheral surface of the prepared conductive substrate was subjected to mirror finishing and wet blasting, and then cleaned. First, as a mirror finish for the surface of the conductive substrate, the conductive substrate was held at both ends and rotated at a high speed of 1500-8000 rpm, and a diamond bite was pressed against it, and burnishing was performed at a feed rate of 0.08-0.5 mm. That is, a diamond bite with a depth in the work rotation direction on the finishing surface of the bite was pressed against the surface of the conductive substrate to obtain a smooth finished surface. After such mirror finishing, the conductive substrate was degreased and washed.

[0106] Next, wet blasting was performed by stirring a high-hardness abrasive such as alumina with water, mixing it with compressed air, accelerating it, and projecting it onto the surface of the mirror-finished conductive substrate to roughen it. With this method, the conductive substrate is rotated while processing, so a highly uniform processed surface can be formed in a short time. Specifically, the following parameters were adjusted as the conditions for the wet blasting process to prepare conductive substrates having different surface roughnesses. Abrasive material and particle size: A (alundum (brown soluble alumina)) #320~#4000 Abrasive concentration: 10~18% Projection air pressure: 0.10~0.35MPa Throw distance (distance between workpiece center and blast head): 20~300mm Projection time: 1 to 60 seconds Workpiece rotation speed: 120~180rpm The surface roughness was adjusted by changing the abrasive material, particle size, concentration, projection air pressure, projection distance and projection time. After wet blasting, the residue remaining on the surface was removed by cleaning to prepare a conductive substrate.

[0107] The conductive substrate thus prepared was subjected to the deposition apparatus shown in FIG. 3 under the film forming conditions shown in Tables 1 and 2 to form layers on the surface of the conductive substrate so as to have the layer structure shown in FIG. 2, thereby producing an a-Si photosensitive member. The first region of the surface protective layer was formed by changing the flow rate of the source gas and the high frequency power as shown in Table 1 so that C / (Si+C) changed continuously. The flow rate of the source gas, the reaction pressure, the high frequency power and the substrate temperature during the formation of the third region of the surface protective layer were set to the conditions shown in Table 2.

[0108] [Table 1]

[0109] [Table 2]

[0110] The surface shapes of the electrophotographic photoreceptors 1 to 9 obtained as described above were measured. The measurements were performed using a Keyence VK-X100 laser microscope, and the surface shape was evaluated using three-dimensional roughness parameters in accordance with ISO25178. Measurement conditions included a lens with a magnification of 100x. As the measurement object was cylindrical, curvature correction was performed in two dimensions, and the arithmetic average roughness Sa was calculated. Measurements were performed at a total of 28 locations on the electrophotographic photosensitive member, including 7 locations in the axial direction (center, ±50 mm, ±100 mm, ±150 mm) and 4 locations in the circumferential direction (every 90°), and the average value was taken as the arithmetic mean roughness Sa of the electrophotographic photosensitive member. The results are shown in Table 3.

[0111] In addition, the number of silicon atoms (Si), the number of carbon atoms (C), and the number of carbon atoms (C) on the surface were analyzed using X-ray photoelectron spectroscopy (hereinafter also abbreviated as XPS). In XPS, elements can be identified and their quantities measured by irradiating the surface of a sample with X-rays and measuring the energy of photoelectrons emitted from the surface of the sample. In the measurement, first, an analysis sample was prepared by cutting out a sample having a size of about 10 mm×10 mm from the center in the axial direction of the electrophotographic photosensitive member. The prepared analysis sample was placed in an XPS analysis device (product name: Quantum 2000 Scanning ESCA, manufactured by PHI Corporation), and first, weak argon sputtering was performed to remove traces of contaminants adhering to the outermost surface. The sample was then irradiated with X-rays, and the excited electrons released were received by a detector. The atomic content on the surface of the sample was calculated from the received energy distribution. From the results obtained, the number of silicon atoms (Si) and the number of carbon atoms (C) on the surface were calculated, and the ratio of the number of carbon atoms (C) to the sum of the number of silicon atoms (Si) and the number of carbon atoms (C) (C / (Si+C)) was calculated. The results obtained are also shown in Table 3.

[0112] [Table 3]

[0113] [Developer manufacturing example] As the resin A, resins A1 to A10 were produced by the following method. (Production example of resin A1) Toluene 150.0 parts Behenyl acrylate (compound represented by the following structural formula (a-1)) 48.0 parts (80.0% by mass) Acrylic acid 12.0 parts Polymerization initiator: Azoisobutyronitrile (AIBN) 1.5 parts The above materials were put into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. The reaction vessel was heated to 70°C while stirring at 200 rpm to carry out a polymerization reaction for 12 hours, and a solution in which the polymer of the monomer composition was dissolved in toluene was obtained. Next, the temperature of the solution was lowered to 25°C, and then the solution was poured into 1000.0 parts of methanol while stirring, and the methanol insoluble matter was precipitated. The obtained methanol insoluble matter was filtered, washed with methanol, and then vacuum dried at 40°C for 24 hours to obtain resin A1. [ka]

[0114] (Production example of resin A2) In the production example of Resin A1, behenyl methacrylate (a compound represented by the following structural formula (a-2)) was used instead of behenyl acrylate. Also, methacrylic acid was used instead of acrylic acid. Resin A2 was produced in the same manner as Resin A1. [ka]

[0115] (Resin A3 manufacturing example) Resin A3 was produced in the same manner as Resin A1 except that a compound represented by the following structural formula (a-3) was used instead of behenyl acrylate in the production example of Resin A1. [ka]

[0116] (Resin A4 manufacturing example) Resin A4 was produced in the same manner as Resin A1 except that a compound represented by the following structural formula (a-4) was used instead of behenyl acrylate in the production example of Resin A1. [ka]

[0117] (Resin A5 manufacturing example) Resin A5 was produced in the same manner as Resin A1 except that a compound represented by the following structural formula (a-5) was used instead of behenyl acrylate in the production example of Resin A1. [ka]

[0118] (Production example of resin A6) Resin A6 was produced in the same manner as Resin A1 except that a compound represented by the following structural formula (a-6) was used instead of behenyl acrylate in the production example of Resin A1. [ka]

[0119] (Resin A7 manufacturing example) Toluene 150.0 parts Behenyl acrylate (compound represented by the above structural formula (a-1)) 60.0 parts (100.0% by mass) Polymerization initiator: Azoisobutyronitrile (AIBN) 1.5 parts Resin A7 was produced in the same manner as Resin A1 except that the above materials were charged into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere.

[0120] (Resin A8 manufacturing example) Toluene 150.0 parts Behenyl acrylate (compound represented by the above structural formula (a-1)) 30.0 parts (50.0% by mass) Acrylic acid 30.0 parts Polymerization initiator: Azoisobutyronitrile (AIBN) 1.5 parts The above materials were charged into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere, and Resin A8 was produced in the same manner as Resin A1.

[0121] (Resin A9 manufacturing example) Toluene 150.0 parts Behenyl acrylate (compound represented by the above structural formula (a-1)) 18.0 parts (30.0% by mass) Acrylic acid 48.0 parts Polymerization initiator: Azoisobutyronitrile (AIBN) 1.5 parts Resin A9 was produced in the same manner as Resin A1 except that the above materials were charged into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere.

[0122] (Production example of resin A10) Toluene 150.0 parts Behenyl acrylate (compound represented by the above structural formula (a-1)) 6.0 parts (10.0% by mass) Acrylic acid 54.0 parts Polymerization initiator: Azoisobutyronitrile (AIBN) 1.5 parts The above materials were charged into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere, and Resin A10 was produced in the same manner as Resin A1.

[0123] Table 4 shows the content ratio of the monomer unit represented by formula (1) relative to the total mass of resin A in resins A1 to A10, and the R 12 The carbon number and melting point of the compound are shown.

[0124] <Measurement of melting point of resin A> The melting point of Resin A was measured using a DSC Q1000 (manufactured by TA Instruments) under the following conditions. Heating rate: 10℃ / min Measurement start temperature: 20℃ End of measurement temperature: 180℃ The melting points of indium and zinc were used to correct the temperature of the detector, and the heat of fusion of indium was used to correct the amount of heat. Specifically, about 5 mg of the sample was weighed out and placed in an aluminum pan, and differential scanning calorimetry was performed. An empty silver pan was used as a reference. The peak temperature of the maximum endothermic peak in the first heating process was taken as the melting point. The maximum endothermic peak refers to the peak with the largest amount of endothermic heat when there are multiple peaks.

[0125] [Table 4]

[0126] (Production example of resin B) Xylene 100.0 parts Styrene 100.0 parts n-Butyl acrylate 10.0 parts Acrylic acid 1.5 parts Dodecanethiol 6.0 parts Carbon tetrabromide 1.0 parts The above materials were put into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. The reaction vessel was heated to 185°C while stirring at 200 rpm to carry out a polymerization reaction for 10 hours. The solvent was then removed, and the mixture was vacuum dried at 40°C for 24 hours to obtain Resin B.

[0127] (Production example of binder resin 1) 80 parts of resin A1 and 20 parts of resin B were mixed and fed to a twin-screw kneader (product name: S5KRC kneader, manufactured by Kurimoto Iron Works, Ltd.) at 52 kg / hour. At the same time, 1.0 part of t-butylperoxyisopropyl monocarbonate was fed as a radical reaction initiator at 0.52 kg / hour, and the mixture was kneaded and extruded at 90 rpm at 160°C for 7 minutes to carry out a crosslinking reaction. The mixture was then mixed while being depressurized to 10 kPa from a vent port to remove the organic solvent. After cooling the mixture, it was coarsely pulverized to 1 mm or less using a hammer mill to obtain binder resin 1.

[0128] (Production Examples of Binder Resins 2 to 10) In the production example of binder resin 1, resins A2 to A10 were used instead of resin A1 as shown in Table 5. Except for the above, binder resins 2 to 10 were produced in the same manner as binder resin 1.

[0129] (Toner core 1 manufacturing example) Binding resin 1 100 parts Aliphatic hydrocarbon compound HNP-51 (manufactured by Nippon Seiro) 10 parts CI Pigment Blue 15:3 6.5 parts 0.5 parts of 3,5-di-t-butylsalicylic acid aluminum compound The above materials were mixed in a Henschel mixer (FM-75, manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 20 s -1 The mixture was mixed at 120°C for a rotation time of 5 min. The mixture was then kneaded at a discharge temperature of 135°C using a twin-screw kneader (PCM-30, manufactured by Ikegai Corporation) set at a temperature of 120°C and a screw rotation speed of 200 rpm. The kneaded mixture was cooled at a cooling rate of 15°C / min and coarsely crushed to 1 mm or less using a hammer mill to obtain a coarsely crushed product. The coarsely crushed product was then finely crushed using a mechanical crusher (T-250, manufactured by Freund Turbo Corporation). Further, classification was performed using Faculty F-300 (manufactured by Hosokawa Micron Corporation) to obtain toner core 1. The operating conditions were a classification rotor rotation speed of 130 s -1 , Dispersion rotor speed 120s -1 It was decided.

[0130] (Toner core 2-10 manufacturing example) In the production example of toner particle 1, binder resin 2 to binder resin 10 were used instead of binder resin 1 as shown in Table 5. Except for that, toner cores 2 to 10 were produced in the same manner as toner core 1.

[0131] [Table 5]

[0132] (Example of toner shell 1 formation) A glass reaction vessel equipped with a stirrer and a thermometer blade was set in a water bath, and 300 parts of ion-exchanged water was placed in the glass reaction vessel. Then, the temperature inside the glass reaction vessel was kept at 30° C. using a water bath. Subsequently, 30 parts of an aqueous solution of an oxazoline group-containing polymer as a toner shell raw material (product name: EPOCROS (registered trademark) WS-300, manufactured by Nippon Shokubai Co., Ltd., solid content concentration: 10% by mass) was placed in the glass reaction vessel, and the contents of the glass reaction vessel were then stirred. Subsequently, 300 parts of each of the toner cores 1 to 10 obtained by the above-mentioned procedure was added to the glass reaction vessel, and the contents of the glass reaction vessel were stirred at a rotation speed of 200 rpm for 1 hour. Thereafter, 300 parts of ion-exchanged water was added to the glass reaction vessel, and further, 6 parts of ammonia water (ammonia concentration: 1% by mass) was added to the glass reaction vessel. Subsequently, while stirring the contents of the glass reaction vessel at a rotation speed of 150 rpm, the temperature inside the glass reaction vessel was raised to 60° C. at a rate of 0.5° C. / min. The contents of the glass reaction vessel were then stirred at a rotation speed of 100 rpm and kept at that temperature (60° C.) for 1 hour. While the temperature of the contents of the glass reaction vessel was maintained at 60° C., a toner shell was formed covering the surfaces of the toner cores 1 to 10, thereby obtaining toner particles 1 to 10. The toner shell was composed of the specific vinyl resin described above.

[0133] Next, ammonia water (ammonia concentration: 1% by mass) was added to the glass reaction vessel to adjust the pH of the glass reaction vessel content to 7, and then the glass reaction vessel content was cooled to room temperature (25°C) to obtain a dispersion liquid containing toner particles 1 to 10. The obtained dispersion of toner particles 1 to 10 was filtered (solid-liquid separation) using a Buchner funnel to obtain wet cake-like toner particles 1. The wet cake-like toner particles 1 were redispersed in ion-exchanged water and then filtered using a Buchner funnel. Furthermore, the redispersion and filtration were repeated five times to wash the toner particles 1 to 10. Next, the washed toner particles 1 to 10 were dried using a continuous surface modification device ("Coatmizer (registered trademark)" manufactured by Freund Corporation) under conditions of a hot air temperature of 45°C and a blower air volume of 2 m3 / min. By the above method, the toner shell 1 was formed on the surface of the toner cores 1 to 10.

[0134] (Examples of toner shell formation 2 to 5) In the example of forming toner shell 1, the toner core used was toner core 1, and the reaction time was adjusted to form toner shells 2 to 5 with shell thicknesses adjusted as shown in Table 6, thereby obtaining toner particles 12 to 15. The toner core and toner shell of each of the obtained toner particles are shown in Table 7.

[0135] (Toner shell thickness measurement) The thickness of the toner shell can be measured by observing a cross section with a transmission electron microscope (TEM) as follows. Using an osmium plasma coater (Filgen, OPC80T), an Os film (5 nm) and a naphthalene film (20 nm) were applied to the toner as a protective film, and the toner was embedded in a photocurable resin D800 (JEOL). Then, a toner cross section with a film thickness of 60 nm (or 70 nm) was prepared using an ultrasonic ultramicrotome (Leica, UC7) at a cutting speed of 1 mm / s. The obtained cross section was stained for 15 minutes in a RuO4 gas atmosphere of 500 Pa using a vacuum electron staining apparatus (Filgen, VSC4R1H) and observed using a STEM (JEOL, JEM2800). The STEM probe size was 1 nm, and the image size was 1024 × 1024 pixels. The obtained images were binarized (threshold value 120 / 255 level) using image processing software [Image-Pro Plus (Media Cybernetics)]. The obtained image was binarized to extract the shells in the toner particles and measure their thickness. The thickness of each toner particle was measured at four points (top, bottom, left and right) and the average shell thickness per toner particle was calculated. The same measurement was performed on 20 randomly selected toner particles, and the average value was calculated to obtain the average thickness of the toner shell.

[0136] [Table 6]

[0137] [Table 7]

[0138] (Production Example of Resin Particle 1) A glass reaction vessel equipped with a stirrer, a condenser, a thermometer and a nitrogen inlet tube was placed in a water bath. The following materials were added to the glass reaction vessel while stirring. 100 parts butyl methacrylate 20 parts styrene 6 parts sodium dodecylbenzenesulfonate (DBS) as an emulsifier Benzoyl peroxide (BPO) 15 parts as polymerization initiator 600 parts deionized water While introducing nitrogen gas into the glass reaction vessel, the contents of the glass reaction vessel were reacted (copolymerized) under stirring. In this reaction, the reaction temperature X was 100°C, the reaction time Y was 3 hours, and the stirring speed Z was 1,000 rpm. The reaction solution (emulsion solution) after the reaction was dried to obtain resin particles 1.

[0139] (Production Examples of Resin Particles 2 to 13) In the production example of resin particles 1, the type and mass of the resin added as a raw material were changed to the conditions shown in Table 8. In addition, the reaction time and stirring speed were adjusted to adjust the number average primary particle size to the value shown in Table 8.

[0140] (Measurement of number average primary particle size) The number average primary particle size of each of the resin particles 1 to 13 was measured by the following method. Using a field emission scanning electron microscope (FE-SEM, product name: JSM-3000, manufactured by JEOL Ltd.), the measurement sample (resin particles) was observed at a magnification of 100,000 times. Ten resin particles were randomly selected from the resin particles observed in the field of view of the microscope. The primary particle size (the diameter of a circle having the same area as the projected area of ​​the resin particle, i.e., the circle equivalent diameter) of each of the selected 10 resin particles was measured. The sum of the primary particle sizes of the 10 resin particles was divided by the number of resin particles measured (10). This allowed the number-average primary particle size of the resin particles to be calculated. The measurement results are shown in Table 8.

[0141] [Table 8]

[0142] <Production Example of Magnetic Carrier Core Particles> ·Fe2O362.7 parts ·MnCO329.5 parts ·Mg(OH)26.8 parts ·SrCO31.0 parts The ferrite raw materials were weighed so that the above materials had the above composition ratio. The mixture was then pulverized and mixed for 5 hours using a dry vibration mill with stainless steel beads, and the pulverized material was then made into pellets of approximately 1 mm square using a roller compactor. The pellets were passed through a vibrating sieve with 3 mm openings to remove coarse powder, and then through a vibrating sieve with 0.5 mm openings to remove fine powder. The pellets were then fired in a burner-type firing furnace at 1000°C for 4 hours in a nitrogen atmosphere (oxygen concentration 0.01% by volume) to produce pre-sintered ferrite. The calcined ferrite was crushed to about 0.3 mm using a crusher, and then 30 parts of water was added to 100 parts of the calcined ferrite, and the mixture was crushed in a wet ball mill for 1 hour using zirconia beads. The resulting slurry was further crushed in a wet ball mill for 4 hours to obtain a ferrite slurry (finely crushed calcined ferrite). To the ferrite slurry, 1.0 part of ammonium polycarboxylate as a dispersant and 2.0 parts of polyvinyl alcohol as a binder were added per 100 parts of calcined ferrite, and the mixture was granulated into spherical particles using a spray dryer (manufacturer: Okawara Kakoki). After adjusting the particle size of the resulting particles, the mixture was heated at 650°C for 2 hours using a rotary kiln to remove the organic components of the dispersant and binder. In order to control the firing atmosphere, the material was heated from room temperature to 1300°C in a nitrogen atmosphere (oxygen concentration 1.00% by volume) in an electric furnace over a period of 2 hours, and then fired at 1150°C for 4 hours. The material was then cooled to 60°C over a period of 4 hours, returned from the nitrogen atmosphere to the air, and removed at a temperature of 40°C or less. After crushing the agglomerated particles, low magnetic particles were removed by magnetic separation, and coarse particles were removed by sieving through a sieve with 250 μm openings to obtain magnetic carrier core particles with a volume-based 50% particle size (D50) of 37.0 μm.

[0143] <Magnetic Carrier 1 Manufacturing Example> In the first coating step, a thermosetting silicone resin solution (methyl silicone resin) was applied to the magnetic carrier core particles 1. The amount of coating resin was set to 0.20 parts per 100 parts of magnetic core particles. For coating, a coating device was used that was provided with a rotating bottom plate disk and stirring blades in a fluidized bed to form a swirling flow while coating. The above-mentioned resin solution was sprayed from a direction perpendicular to the direction of movement of the fluidized bed in the device. Next, the following materials were prepared: Fluororesin solution (a mixture of tetrafluoroethylene and hexafluoropropylene (FEP)) (1.91 parts per 100 parts of magnetic carrier core particles as solid content) Thermosetting melamine resin solution (0.09 parts per 100 parts of magnetic core particles as solid content) These were mixed with sufficient stirring to prepare a carrier coating solution. This coating solution was applied to the magnetic core particles as the second coating process. For coating, a coating device was used that was equipped with a rotating bottom plate disk and stirring blades in a fluidized bed to form a swirling flow while coating. The obtained carrier was then dried in the fluidized bed at a temperature of 280°C for 1 hour to remove the solvent, and magnetic carrier 1 was obtained.

[0144] <Production example of developer 1> The following materials were mixed in a Henschel mixer FM-10C (manufactured by Mitsui Miike Chemical Industry Co., Ltd.) at a rotation speed of 30 s. -1 The mixture was mixed at 10 minutes rotation time to obtain toner 1. 100 parts of toner particles ·Resin particles 1 1.2 parts 2.1 parts of silica particles with an average particle size of 130 nm and surface-treated with hexamethyldisilazane 0.7 parts of silica particles with an average particle size of 20 nm and surface-treated with hexamethyldisilazane Next, the following materials were mixed in a V-type mixer (V-20, manufactured by Seishin Enterprise Co., Ltd.) to obtain developer 1. Toner 1 8.0 parts Magnetic carrier 1 92.0 parts

[0145] <Production examples of developers 2 to 10 and 12> In the production example of developer 1, toner particles 2 to 11 were used instead of toner particles 1. Except for that, developers 2 to 12 were produced in the same manner as developer 1.

[0146] <Production Example of Developer 11> Developer 11 was produced in the same manner as developer 1, except that in the production example of developer 1, toner particles 11 were used instead of toner particles 1 and resin particles 1 were not used.

[0147] <Production Examples of Developers 13 to 24> Resin particles 2 to 13 were used in place of resin particles 1 in the production example of developer 12. Except for that, developers 13 to 24 were produced in the same manner as developer 12.

[0148] <Production Example of Developer 25> Developer 25 was produced in the same manner as in the production example of developer 1, except that resin particles 1 were not used.

[0149] <Production Examples of Developers 26 to 29> In the production example of developer 25, toner particles 12 to 15 were used instead of toner particles 1. Except for that, developers 26 to 29 were produced in the same manner as developer 25.

[0150] Table 9 shows the toner particles and resin particles used in the production of each developer. [Table 9]

[0151] Example 1 A modified Canon image Press C800 copying machine was used as the electrophotographic device. More specifically, to obtain an electrophotographic apparatus having the configuration shown in FIG. 1, the cleaner was modified to have a configuration including a rubbing roller that rubs the electrophotographic photosensitive member with an elastic sponge, and a cleaning blade. The cleaning blade was adjusted to contact with the surface at a contact pressure of 40 g / cm, and the rubbing roller of the cleaner and the cleaning blade were replaced with new parts in order to reproduce the condition at the beginning of use of the electrophotographic apparatus. An electrophotographic photosensitive member 1 was set in the black station of the prepared electrophotographic apparatus, and developer 1 was set in the developing device as the developer.

[0152] (Image evaluation) The image evaluation was performed in an environment of 32° C. / 85% RH. As a chart for evaluation, an A4 size (297 mm×210 mm) chart with one 1.6 mm wide ruled line arranged in the longitudinal direction at 12.5% ​​density was prepared. The printing rate of this evaluation chart is approximately 0.1% (1.6×0.125 / 210), which is a condition in which the amount of toner supplied is small. Under the above conditions, 1000 sheets were printed continuously, and the output images and the operating sounds of the device during printing, i.e., the presence or absence of abnormal sounds, were evaluated according to the following evaluation criteria. The results are shown in Table 10.

[0153] (Evaluation Criteria) S: No abnormal noise is generated, and no image defects are observed in any images. A: A faint abnormal noise was heard during printing, but no image defects were observed in any of the images. B: A faint abnormal noise occurs during the process, and some images are obtained that give the impression of being defective, but the level is such that it is not possible to determine whether the image is clearly defective. C: A faint abnormal noise was generated during printing, and extremely minor image defects occurred in some images. D: An abnormal noise occurs during printing, and there is a clear image defect on the image.

[0154] [Examples 2 to 34, Comparative Examples 1 to 3] As Examples 2 to 34 and Comparative Examples 1 to 3, the combinations of electrophotographic photoreceptors and developers shown in Table 10 were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 10.

[0155] Example 35 The rubbing roller in the cleaner was removed from Example 1, and no rubbing roller was used. Except for this, evaluation was performed in the same manner as in Example 1. The evaluation results are shown in Table 10.

[0156] [Table 10] [Explanation of symbols]

[0157] 101...electrophotographic photoreceptor 102...Charger 103...Image exposure means 104...Developer 105...Intermediate transfer body 106…Cleaner 106a...rubbing roller 106b…Cleaner 107…Pre-exposure device

Claims

1. An electrophotographic photoreceptor; A charging means for charging the surface of the electrophotographic photoreceptor; an image exposure means for irradiating an image exposure light onto the charged surface of the electrophotographic photoreceptor to form an electrostatic latent image on the surface of the electrophotographic photoreceptor; a developing means having a toner and developing the electrostatic latent image with the toner to form a toner image on the surface of the electrophotographic photoreceptor; a transfer means for transferring the toner image from the surface of the electrophotographic photoreceptor to a transfer material in a transfer step; a cleaning means for removing residual toner remaining on the surface of the electrophotographic photoreceptor after the transfer step; a fixing means for fixing the toner image onto the transfer material; An electrophotographic apparatus having the surface of the electrophotographic photoreceptor is formed of hydrogenated amorphous silicon carbide or hydrogenated amorphous carbon; The toner comprises toner particles, The toner particles contain a resin A having a unit represented by the following formula (1), The resin A is a crystalline resin, The content ratio of the unit represented by the following formula (1) in the resin A is 30 mass % or more and 100 mass % or less with respect to the total mass of the resin A: Electrophotographic apparatus characterized in that 【Chemistry 1】 (In formula (1), R 11 represents a hydrogen atom or a methyl group, R 12 represents an alkyl group having 18 to 36 carbon atoms.

2. the toner particles have resin particles on the surface thereof, The resin particles contain a copolymer having a unit represented by the following formula (2) and a unit represented by the following formula (3), a total content ratio of a unit represented by the following formula (2) and a unit represented by the following formula (3) in the resin particles is more than 70 mass % and 100 mass % or less with respect to a total mass of the resin particles:

2. The electrophotographic apparatus according to claim 1. 【Chemistry 2】 (In formula (2), R 21 represents a hydrogen atom or a methyl group, R 22 represents an alkyl group having 1 to 4 carbon atoms.

3. 3. The electrophotographic device according to claim 2, wherein a total content ratio of the unit represented by the formula (2) and the unit represented by the formula (3) in the copolymer is 90% by mass or more and 100% by mass or less with respect to a total mass of the copolymer.

4. 4. The electrophotographic apparatus according to claim 2, wherein the resin particles have a number average primary particle size of 30 nm or more and 150 nm or less.

5. The toner particles have a core containing the resin A and a shell coating the core, The shell contains a resin having an amide bond and an ester bond.

5. The electrophotographic apparatus according to claim 1.

6. 6. The electrophotographic apparatus according to claim 5, wherein the shell has a thickness of 30 nm or more and 60 nm or less.

7. 7. The electrophotographic apparatus according to claim 1, wherein the arithmetic mean roughness Sa of the surface of the electrophotographic photosensitive member is 80 nm or more and 120 nm or less.

8. 8. The electrophotographic apparatus according to claim 1, wherein a ratio C / (Si+C) of the number of carbon atoms (C) to the sum of the number of silicon atoms (Si) and the number of carbon atoms (C) on the surface of the electrophotographic photosensitive member is 0.95 or more and 0.99 or less.

9. The cleaning means is a rubbing roller formed of an elastic sponge for rubbing the electrophotographic photoreceptor; a cleaning blade that is brought into contact with the electrophotographic photosensitive member to remove the residual toner; 9. The electrophotographic apparatus according to claim 1, further comprising:

10. An electrophotographic photoreceptor; a developing means having a toner and developing an electrostatic latent image on the surface of the electrophotographic photoreceptor with the toner to form a toner image on the surface of the electrophotographic photoreceptor; a cleaning means for removing residual toner remaining on the surface of the electrophotographic photoreceptor after the transfer process; a process cartridge which is detachably mountable to a main body of an electrophotographic apparatus and which integrally supports the the surface of the electrophotographic photoreceptor is formed of hydrogenated amorphous silicon carbide or hydrogenated amorphous carbon; the toner having toner particles; The toner particles contain a resin A having a unit represented by the following formula (1), The resin A is a crystalline resin, The content ratio of the unit represented by the following formula (1) in the resin A is 30 mass % or more and 100 mass % or less with respect to the total mass of the resin A: A process cartridge comprising: 【Chemistry 3】 (In formula (1), R 11 represents a hydrogen atom or a methyl group, R 12 represents an alkyl group having 18 to 36 carbon atoms.

11. a charging step of charging the surface of an electrophotographic photoreceptor; an image exposure step of irradiating the charged surface of the electrophotographic photoreceptor with image exposure light to form an electrostatic latent image on the surface of the electrophotographic photoreceptor; a developing step of developing the electrostatic latent image with a toner to form a toner image on the surface of the electrophotographic photoreceptor; a transfer step of transferring the toner image from the surface of the electrophotographic photoreceptor to a transfer material; a cleaning step for removing residual toner remaining on the surface of the electrophotographic photoreceptor after the transfer step; An image forming method comprising the steps of: the surface of the electrophotographic photoreceptor is formed of hydrogenated amorphous silicon carbide or hydrogenated amorphous carbon; the toner having toner particles; The toner particles contain a resin A having a unit represented by the following formula (1), The resin A is a crystalline resin, The content ratio of the unit represented by the following formula (1) in the resin A is 30 mass % or more and 100 mass % or less with respect to the total mass of the resin A:

1. An image forming method comprising: 【Chemistry 4】 (In formula (1), R 11 represents a hydrogen atom or a methyl group, R 12 represents an alkyl group having 18 to 36 carbon atoms.

12. The cleaning step comprises: a step of rubbing the electrophotographic photoreceptor with an elastic sponge; a step of contacting a cleaning blade with the electrophotographic photoreceptor to remove the residual toner; The image forming method according to claim 11, comprising:

Citation Information

Patent Citations

  • Image forming method

    JP1989177582A

  • Capsuled toner composite

    JP1991174162A

  • Electrophotographic device

    JP2001142371A

  • Image forming device

    JP2002174915A

  • Electrophotographic device

    JP2003195713A